Influence of exercise and sports on bone - Naomi Omi (Japanese Society of Physical Fitness and Sports Medicine, 2014)
In general, exercise and/or sports are effective for bone health. Bone metabolism is influenced by several environmental factors, especially mechanical loading and nutrition. It is well known that the bone mass in athletes is higher than that of people having a sedentary lifestyle. Mechanical loading leads to an increase in bone mass, whereby it helps in strengthening. However, in some cases athletes might have lower bone mass. Insufficient dietary intake and an imbalanced nutritional status cause an inhibition of bone formation and activation of bone resorption. A higher than necessary Ca intake is important for improving bone metabolism. An adequate protein intake level, not too high or low, might be effective for bone maintenance. In addition, low energy availability could be leading to low bone mass. It might be possible to say that exercise is not effective for improving bone metabolism in an inadequate and/or imbalanced nutritional condition. A moderate level of physical activity, not an excess level, and appropriate nutrient intake are both necessary for bone health.